Caffeic Acid Phenethyl Ester Alleviates Cryodamage To Lung Cancer Cells During Cryopreservation - Ezgi Avşar Abdik (Hittite Journal of Science and Engineering, 2021)
Cryopreservation is widely used technique for long-term preservation of viable cells at low temperature. In this process, considering the effects of cryodamage on cells, the application of safe and efficient cryoprotective agents is very important. Caffeic acid phenethyl ester (CAPE) is a natural biological compound which is found in propolis extract and possess beneficial effects such as anti-oxidant, antimicrobial, anti-inflammatory. In the current study was to investigate the cryoprotective effects of CAPE on human lung cancer cell line, A549. Firstly, cells were cryopreserved in freezing medium with/without different concentrations of CAPE (5, 10, and 20 μM). The cells were frozen slowly and kept in liquid nitrogen for one month. After thawing, the cryoprotective effects of CAPE were determined by cell viability, proliferation, colony formation, and gene expression levels. The results showed that 5μM CAPE supplemented freezing medium significantly increased the viability of post thaw A549 cells. 5μM CAPE treatment significantly increased cell proliferation after 24, 48 and 72h since thawing compared to control. 10 μM CAPE did not significantly affect cell viability compared to control group. Also, 5μM CAPE increased the number of A549 colonies compared to 10μM CAPE and control groups. Furthermore, markedly larger colonies were noticed in 5μM CAPE group. In addition, 5μM CAPE significantly increased apoptosis and proliferation-related genes, Akt, NFκB and Bcl-2, expression levels compared to 10μM CAPE and control groups. CAPE may be a potential cryoprotective agent for relieving cryodamage during cryopreservation.